Analiza rabe označevalcev napak - Kokove-Hrovat, Maja (Knjižnica, 2004)
Publishers' errors are not uncommon in publications. In bibliographic records, cataloguers use error indicators to indicate them. They must follow cataloguing rules. An analysis of the recent use of the error indicators sic and i. e. was made in the Slovenian union catalogue COBIB. Error indicators were searched for in the place of publication, in the publishers' name and in the title. The results were arranged in different categories and analysed. Cataloguers' mistakes were also analysed. Finally some sugestions are presented for more effective searching and discovering of publishers' errors and their proper indication. Above all, we tried to emphasize the use of cataloguing rules.
Keywords: katalogizacija; vzajemni katalogi; katalogizacijska pravila; označevalci napak